Biowaiver Monographs for Immediate‐Release Solid Oral Dosage Forms: Nifedipine. Issue 10 (6th July 2015) - Gajendran, Jayachandar; Krämer, Johannes; Shah, Vinod P.; Langguth, Peter; Polli, James; Mehta, Mehul; Groot, D.W.; Cristofoletti, Rodrigo; Abrahamsson, Bertil; Dressman, Jennifer B.
<x xml:space="preserve">Abstract</x> Literature data relevant to the biopharmaceutical properties of the active pharmaceutical ingredient (API) nifedipine are reviewed to evaluate whether a waiver of in vivo bioequivalence (BE) testing of immediate‐release (IR) dosage forms formulated as tablets and soft gelatin capsules is warranted. Nifedipine's solubility and permeability, its therapeutic use and index, pharmacokinetics, food drug interactions, and any reported BE/bioavailability problems were all taken into consideration. Solubility and BA data indicate conclusively that nifedipine is a class II substance of biopharmaceutics classification system (BCS) and that the formulation of drug product plays a key role on the dissolution characteristics of the API. Therefore, a BCS biowaiver‐based approval of nifedipine containing IR oral dosage forms cannot be recommended for reformulated/new multisource drug products or for major scale‐up and postapproval changes to the existing drug products. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3289–3298, 2015